OIL-OIL CORRELATION BASED ON ORGANIC GEOCHEMICAL PARAMETERS USING MULTIVARIATE ANALYSIS METHODS IN THE NORTH SUMATERA BASIN - Reyhan Mahardhika, Farrel
Twenty oil samples were collected from thirteen oil fields distributed throughout the area of the North Sumatera Basin. A number of organic geochemical parameters were measured from those oil samples. Organic oil geochemical data such as biomarker ratio and 13C carbon isotope fraction were used as the geochemical data matrix to perform the oil-oil correlation in this study. The aim of this study is to determine the families of the available oil samples using multivariate statistical methods, to determine the characteristics of each oil family, and to determine the source rocks of each oil family hypothetically based on the interpretation of the characteristics of the oil family found in the North Sumatera Basin area. Oil-oil correlation is carried out using two multivariate statistical methods. The results showed that there were two oil families found in the study area, namely the Red Family oil group and the Blue Family oil group. The Red Family oil group is likely to come from a suboxic, marine environment with an algaedominant organic material input, while the Blue Family oil group is likely derived from a suboxic, fluvio-deltaic (transitional) environment with a predominantly terrestrial organic material input. Based on the interpretation of the geochemical characteristics of each oil families, it is likely that the Red Family oil group were sourced from the lower part of the Baong Formation source rocks, while the Blue Family oil group were potentially sourced from the Bampo Formation source rocks.